Pre- and postnatal polychlorinated biphenyl exposure and cognitive and behavioral development at age 45 Months in a cohort of Slovak children - Simeone, Regina M; Howards, Penelope P; Anderson, Elizabeth; Jusko, Todd A; Drobná, Beata; Kočan, Anton; Čonka, Kamil; Fabišiková, Anna; Murínová, Ľubica Palkovičová; Canfield, Richard L; Sonneborn, Dean; Wimmerová, Soňa; et al. (Chemosphere, 2022)
Evidence of associations of pre- and postnatal exposure to polychlorinated biphenyls (PCBs) with cognitive development beyond early childhood is inconsistent. A previous report from this cohort observed adverse associations between early life PCB exposures and infant Bayley scores at age 16 months. The present study examines pre- and postnatal PCB exposures in relation to both behavior and cognitive development at age 45 months. Participants were 472 mother-child pairs residing in an area of eastern Slovakia characterized by environmental contamination with PCBs, which resulted in elevated blood serum concentrations. PCB-153 and PCB-118 concentrations were measured in maternal and in infant 6-, 16-, and 45-month serum samples. At age 45 months, children were administered five subtests of the Wechsler Preschool and Primary Scale of Intelligence (WPPSI-III), and mothers completed the Child Behavior Checklist (CBCL). Negative binomial and multiple linear regressions were used to estimate PCB-CBCL and PCB-WPPSI-III subtest score associations, respectively. Pre- and postnatal levels of PCB-153 and PCB-118 were not associated with cognitive performance on the WPPSI-III in this cohort. There was some suggestion that higher postnatal PCB concentrations were associated with more sleep problems and feelings of depression and anxiousness.
Keywords: Environmental Pollutants; látky znečišťující životní prostředí; Child behavior checklist; vystavení vlivu životního prostředí; Cognition; těhotenství; kojenec; polychlorované bifenyly; Cohort Studies; Infant; Environmental Exposure; kohortové studie; Slovakia; kognice; Child, Preschool; Slovenská republika; Polychlorinated Biphenyls; Wechsler preschool and primary scale of intelligence-III; ženské pohlaví; Humans; předškolní dítě; Pregnancy; zpožděný efekt prenatální expozice; Polychlorinated biphenyls; Female; Prenatal Exposure Delayed Effects; lidé